Antimicrobial performance of lignin embedded in bacterial nanocellulose membranes - Padrão, Jorge (2021)
The development of bio-based antimicrobial polymeric composites has never been so urgent. Novel antimi- crobial fibrous-based biocomposites will certainly allow the development of important solutions to fight the present and future Pandemics, while reducing the dependence of petrochemical based polymers and fibers. Lignin has a pivotal function in preventing the invasion of phytopathogens, thus, this work explores the anti- microbial potential of lignin when embedded in a biosynthesized fibrous nanomatrix with superior mechanical properties: bacterial nanocellulose (BNC). Lignin was subjected to alkali treatment to promote the inclusion of lignin within BNC which comprises pores ranging from 20 to 300 nm. Both alkali treatment efficiency, bac- tericidal and antiviral activities were investigated